Penerapan alat permainan edukatif (APE) dalam pembelajaran kelas rendah: studi kasus di MI Ma'arif Mulyasari 1 - Siti Uswatun Hasanah; Johar Alimuddin; Rina Rizki Amalia (Piramida Akademi, 2026)
This study aims to deeply analyze the implementation of Educational Teaching Aids (APE) in lower-grade learning at MI Ma'arif 1 Mulyasari and evaluate its impact on student learning development. Using a qualitative descriptive approach, the research subjects involved 5 classroom teachers and 109 students. Data were collected through observation, interviews, and documentation. The results indicate that the mapping of APE typology is carried out in an adaptive tiered manner matching the cognitive structure of the concrete operational phase of children aged 7–9 years. Data analysis carried out qualitatively refers to the Miles and Huberman model, namely data reduction, data presentation, drawing conclusions. The successful implementation of the media is supported by systematic teacher instructional management through curricular planning, interactive execution based on a